2021
DOI: 10.1002/dvg.23457
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive short‐pulsed illumination efficiently activates photoactivatable‐Cre as continuous illumination in embryonic stem cells and pre‐implantation embryos of transgenic mouse

Abstract: Summary The Cre‐loxP system has been widely used for specific DNA recombination which induces gene inactivation or expression. Recently, photoactivatable‐Cre (PA‐Cre) proteins have been developed as a tool for spatiotemporal control of the enzymatic activity of Cre recombinase. Here, we generated transgenic mice bearing a PA‐Cre gene and systematically investigated the conditions of photoactivation for the PA‐Cre in embryonic stem cells (ESCs) derived from the transgenic mice and in a simple mathematical model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…According to this report, the function of the Cre/loxP system was confirmed to be normal (Figure S2). Recent studies have also shown that selective marker genes can be successfully removed from transgenic mammalian cells by the Cre/loxP system (Bittel et al, 2021; Kishi et al, 2021). Considering that Cre recombinase was isolated from Coliphage P1 virus (Sauer & Henderson, 1988) and combining previous reports (Nolden et al, 2006b; Peitz, Pfannkuche, Rajewsky, & Edenhofer, 2002), using prokaryotic expression to produce a cell‐permeable NLS‐TAT‐Cre recombinase may retain its activity.…”
Section: Discussionmentioning
confidence: 99%
“…According to this report, the function of the Cre/loxP system was confirmed to be normal (Figure S2). Recent studies have also shown that selective marker genes can be successfully removed from transgenic mammalian cells by the Cre/loxP system (Bittel et al, 2021; Kishi et al, 2021). Considering that Cre recombinase was isolated from Coliphage P1 virus (Sauer & Henderson, 1988) and combining previous reports (Nolden et al, 2006b; Peitz, Pfannkuche, Rajewsky, & Edenhofer, 2002), using prokaryotic expression to produce a cell‐permeable NLS‐TAT‐Cre recombinase may retain its activity.…”
Section: Discussionmentioning
confidence: 99%